Manajemen Sarana dan Prasarana di Madrasah Ibtidaiyah Unggulan Manna Was Salwa - Tiara Erza Putri; Lisya Maulida Salma Hasanah; Rheva Angelica Wibowo; Rifka Damayanti; Ayu Wulandari (CV Putra Publisher, 2024)
This study aims to analyze the management of infrastructure facilities at MI Unggulan Manna Was Salwa as an effort to support learning efficiency. Infrastructure management is a facility management activity to support the implementation of optimal teaching activities in educational institutions. This research uses a qualitative approach with descriptive methods. Data were collected through direct observation, in-depth interviews with those responsible for managing infrastructure facilities, and analysis of related documentation. The main informants of the study included the madrasah head, administrative staff, and teachers. Data analysis was conducted systematically through three stages: data reduction, data presentation, and conclusion drawing. The results show that infrastructure management at MI Unggulan Manna Was Salwa involves five main stages, namely planning, procurement, maintenance, inventory, and elimination. In the planning stage, the focus is directed at identifying infrastructure needs in accordance with the curriculum and the number of students. The procurement stage involves transparent budget management. The maintenance stage is carried out periodically to ensure the continuity of facility functions. Inventory is carried out with detailed data collection of all facilities, while the deletion stage is applied to facilities that are no longer suitable for use. Theoretically, this study contributes to the development of literature related to educational infrastructure management, especially in the context of madrasah. Practically, the results of this study can serve as a guide for other educational institutions in managing infrastructure effectively and efficiently to support learning activities. Thus, this research is expected to encourage the improvement of the quality of education through optimal facility management.